Understanding fungal potential in the mitigation of contaminated areas in the Czech Republic: tolerance, biotransformation of hexachlorocyclohexane (HCH) and oxidative stress analysis - Russo, Fabiana; Ceci, Andrea; Maggi, Oriana; Siciliano, Antonietta; Guida, Marco; Petrangeli Papini, Marco; Černík, Miroslav; Persiani, Anna Maria (Environmental science and pollution research international, 2019)
The study of the soil microbial community represents an important step in better understanding the environmental context. Therefore, biological characterisation and physicochemical integration are keys when defining contaminated sites. Fungi play a fundamental role in the soil, by providing and supporting ecological services for ecosystems and human wellbeing. In this research, 52 soil fungal taxa were isolated from in situ pilot reactors installed to a contaminated site in Czech Republic with a high concentration of hexachlorocyclohexane (HCH). Among the identified isolates, 12 strains were selected to evaluate their tolerance to different isomers of HCH by using specific indices (Rt:Rc; T.I.) and to test their potential in xenobiotic biotransformation. Most of the selected taxa was not significantly affected by exposure to HCH, underlining the elevated tolerance of all the tested fungal taxa, and different metabolic intermediates of HCH dechlorination were observed. The oxidative stress responses to HCH for two selected species, Penicillium simplicissimum and Trichoderma harzianum, were investigated in order to explore their toxic responses and to evaluate their potential functioning in bioremediation of contaminated environments. This research suggests that the isolated fungal species may provide opportunities for new eco-friendly, integrated and cost-effective solutions for environmental management and remediation, considering their efficient adaptation to stressful conditions.
Keywords: Fungi; oxidační stres; Biodegradation, Environmental; Biotransformation; Ecosystem; Drug Tolerance; Česká republika; hexachlorcyklohexan; houby; látky znečišťující půdu; Soil Microbiology; tolerance léku; Soil; Soil Pollutants; Czech Republic; Isomerism; biotransformace; isomerie; ekosystém; půdní mikrobiologie; Trichoderma; Hexachlorocyclohexane; půda; Oxidative Stress; Penicillium; biodegradace